2023
DOI: 10.1002/chem.202203228
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Reduction of CO2 Coupled with Organic Conversion to Selectively Synthesize High‐Value Chemicals

Abstract: The electrochemical process of coupling electrocatalytic CO2 reduction and organic conversion reaction can effectively reduce the reaction overpotential and obtain value‐added chemicals. Moreover, because of the diversity of substrates and the designability of coupling forms, more and more attention has been paid to this field. This review systematically summarizes the research progress of coupling electrolysis in recent years, (1) co‐electrolysis of CO2 and organics at the cathode to obtain specific products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The necessary reduction potential is therefore outside the photoreducing capabilities of ruthenium and iridium catalysts commonly used in visible-light photoredox catalysis (the highest reduction potential available, tris­[2-phenylpyridinato- C 2 , N ]­iridium­(III), E 1/2 red = −2.19 V vs SCE in acetonitrile) . To access the requisite driving force for CO 2 reduction, prior efforts required ultraviolet (UV) light under flow conditions, visible light with stoichiometric thiolate promoters, or deeply reducing electrodes. As compound 2 has a very negative reduction potential (−2.76 V vs Fc/Fc + ), it should be capable of performing SET reduction of CO 2 without the need for an ultraviolet or visible-light photoredox catalyst. To support this, compound 2 was reacted with carbon dioxide (CO 2 , 1 bar) in pyridine at room temperature, from which a salt compound [ 3 ]­[O 2 CNC 5 (H) 5 –C 5 (H) 5 NCO 2 ] containing 4,4′-di-hydrobipyridyl-di- N -carboxylate dianion was isolated as an orange crystalline solid (yield: 83%, Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The necessary reduction potential is therefore outside the photoreducing capabilities of ruthenium and iridium catalysts commonly used in visible-light photoredox catalysis (the highest reduction potential available, tris­[2-phenylpyridinato- C 2 , N ]­iridium­(III), E 1/2 red = −2.19 V vs SCE in acetonitrile) . To access the requisite driving force for CO 2 reduction, prior efforts required ultraviolet (UV) light under flow conditions, visible light with stoichiometric thiolate promoters, or deeply reducing electrodes. As compound 2 has a very negative reduction potential (−2.76 V vs Fc/Fc + ), it should be capable of performing SET reduction of CO 2 without the need for an ultraviolet or visible-light photoredox catalyst. To support this, compound 2 was reacted with carbon dioxide (CO 2 , 1 bar) in pyridine at room temperature, from which a salt compound [ 3 ]­[O 2 CNC 5 (H) 5 –C 5 (H) 5 NCO 2 ] containing 4,4′-di-hydrobipyridyl-di- N -carboxylate dianion was isolated as an orange crystalline solid (yield: 83%, Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the sluggish kinetics of the OER and the low industrial value of the O 2 produced at the anode significantly reduce the competitiveness and economic feasibility of this process. In this way, coupling more valuable anodic reactions with CO 2 electroreduction has been the subject of recent and valuable contributions and has emerged as a promising approach to lower the overall cell voltage, and consequently the energy efficiency of the system, and also to simultaneously produce high-added-value products both at the cathode and anode. Among the different anodic processes used as paired reactions with CO 2 RR, the electrooxidation of glycerol (GOR, glycerol oxidation reaction) to high-added-value products is one of the most interesting alternatives. ,,,, Glycerol is the major waste product from biodiesel production and can be electrochemically oxidized into a variety of valuable chemicals. In this sense, Verma et al demonstrated that coupling CO 2 RR with the electrooxidation of glycerol reduced the power consumption of the system by 53% compared to use of the OER as anodic process.…”
Section: Introductionmentioning
confidence: 99%
“…53–56 The electrochemical CO 2 reduction reaction (eCO 2 RR) is a highly promising approach since a wide variety of desired products are possible, such as carbon monoxide (CO), 57–60 formic acid (HCOOH), 61–64 methanol (MeOH), 65–69 methane (CH 4 ) 70–72 and even ethylene, 73–76 ethanol (EtOH) 77–80 and other C 2+ products. 81–87 Capturing a reactive intermediate of the eCO 2 RR with a second substrate creates structural motives ubiquitous in the chemical industry, 88–90 expanding the product scope significantly and highlighting the versatility of the eCO 2 RR. Owing to this large pool of high-value products and the sustainable benefits of eCO 2 RR, industrial viability is already being thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%